From manga to film: gender, precarity and the textual transformation of Air Doll. (11th March 2019) - Lewis, Diane Wei
Abstract: This essay situates the Japanese film Kūki ningyō / Air Doll (Koreeda Hirokazu, 2009) and the manga upon which it was based, Gōda tetsugakudō: Kūki ningyō / Gōda Temple of Philosophy: Air Doll by Gōda Yoshiie, within the context of discourses on precarity in contemporary Japan. In Air Doll, a blow-up sex doll comes to life and tries to find love, but fails to connect with alienated Tokyoites. Whereas Gōda's original manga focuses on dysfunctional masculinity and the artificial management of emotion in late-capitalist society, Koreeda's film adaptation deals more broadly with miserable singles, broken families, and a pervasive sense of disconnection. In the film, the air doll's acquisition of an identity through imitation is contrasted with the unhappy function that role-play, repetition and substitution play in real people's lives. The movie begins as a lightly comic and largely affirmative depiction of mimesis as learning, transformation and aspiration. However, imitation soon becomes a trope for emptiness and failure. Gōda's manga critiques the role that rigid gender roles play in late capitalism, but Koreeda's emphasis on the air doll's 'emptiness', her failure to find love, and the collapse of the family evince a melancholic attachment to heteronormative ideals that played a central part in Japan's postwar high-growth economy. Close analysis of both texts reveals how Koreeda's use of live action performance and other original contributions rework the manga's themes.